The Institutionalization of Paramilitarism in Yugoslav Macedonia: The Case of the Organization Against the Bulgarian Bandits, 1923–19331. Issue 3 (3rd July 2019) - Tasić, Dmitar
ABSTRACT: The immediate post-WWI period in Europe was marked by the appearance of numerous paramilitary groups and movements. While they were a consequence of the First World War, in the Balkans they were bearers of a lively and indigenous tradition, originating from Ottoman times. The Bulgarian komitajis of the IMRO and Serbian chetniks quickly adjusted to the new circumstances and continued their rivalries as well as internal clashes. One of such conflicts within the IMRO led to the appearance of a completely new paramilitary organization in Yugoslav Macedonia. Sponsored and organized by the Yugoslav state, a group of IMRO renegades participated in the creation of so-called Organization Against the Bulgarian Bandits, thus contributing to the institutionalization of paramilitarism in this troubled region.